COMMUNITY PARTICIPATION IN DEVELOPMENT IN TARUMAJAYA DISTRICT, BEKASI REGENCY - Hendrik Ismail Syaleh; Nani Nurani Muksin; Rahmat Salam (Jurnal Riset Multidisiplin Edukasi, 2026)
Community participation in development plays a very important role in the implementation of every regional development program, whether in villages or sub-districts, where the community is one of the key elements in the implementation of development and also a key factor in supporting the success of development at the sub-district level. Community involvement not only increases the effectiveness of development program implementation, but also strengthens a sense of ownership and responsibility for the results of development. This study aims to determine the level of community participation in the development process in sub-districts. The research method used is a qualitative descriptive approach through observation, interviews, and documentation. This study shows that community participation is still lacking, with the main factors being the level of education, knowledge about development, indifference, and a lack of community initiative. Therefore, it is necessary to increase community participation so that the community is involved in every stage of development. This is expected to encourage the achievement of sustainable community welfare.